Clinical Features and Outcome of Children with Severe Lower Respiratory Tract Infection Admitted to a Pediatric Intensive Care Unit in South Africa. (9th March 2018) - Hutton, Hayley K; Zar, Heather J; Argent, Andrew C
Abstract: Aim: Severe acute lower respiratory tract infection (ALRTI) remains an important cause of childhood morbidity and mortality. Methods: This is a 12-month retrospective cohort study of children (0–12 years) admitted to a pediatric intensive care unit (PICU) with ALRTI to investigate risk factors, clinical course and in-hospital survival. Results: In total, 265 patients (median age = 4 months [2–12 months]) were identified. In all, 102 (38.5%) had co-morbid disease. Twenty-seven (10.2%) were HIV-infected and 87 (32.8%) were HIV-exposed. In-hospital mortality was 34 (12.8%)—24 (9.1%) in PICU and 10 in the wards. Median duration of intensive care unit was 4.0 days (2.0–8.0) and hospital stay was 12.5 days (7.9–28.0). In total, 192 (72.5%) children required invasive ventilation and 42 (15.8%) required inotropic support. Risk factors for mortality included severe malnutrition (odds ratio [OR] = 8.25; 95% confidence interval [CI] = 1.47–46.21), informal housing (OR = 11.87; CI = 1.89–20.81) or inotropic support (OR = 44.35; CI = 8.20–239.92). HIV exposure or infection was associated with a longer duration of hospital stay (OR = 4.41; CI = 2.44–6.39). Conclusion: Severe ALRTI is associated with a high mortality with several factors impacting on in-hospital survival.